The Use of New Technologies in Crisis Communication within School Organizations - Tureac, Cornelia; Stanciu, Lidia; Panaitescu, Manuela; Macovei, Cristian (Didactica Danubiensis, 2023)
Living in an era where new technologies govern our entire activity, it goes without saying that managers of educational institutions must rethink the ways of approaching crises that can affect the organizations they lead. Rethinking communication in such situations will certainly be different from the “classic” methods recommended by the supporters of traditional approaches. Communication in the online environment is vital for any organization or person who wants to stay at the top, to be successful, to promote their services, offers, and image as well as possible.